Autophagy resolves early retinal inflammation in Igf1-deficient mice - Ana I. Arroba; Lourdes Rodríguez-de la Rosa; Silvia Murillo-Cuesta; Laura Vaquero-Villanueva; Juan M. Hurlé; Isabel Varela-Nieto; Ángela M. Valverde (The Company of Biologists, 2016)
Insulin-like growth factor-1 (IGF-1) is a growth factor with differentiating, anti-apoptotic and metabolic functions in the periphery, and anti-inflammatory properties in the nervous system. Mice that have mutations in the Igf1 gene, rendering the gene product inactive (Igf1−/−), present with age-related visual loss accompanied by structural alterations in the first synapses of the retinal pathway. Recent advances have revealed a crucial role of autophagy in immunity and inflammation. Keeping in mind this close relationship, we aimed to decipher these processes in the context of the defects that occur during ageing in the retina of Igf1−/− mice. Tnfa and Il1b mRNAs, and phosphorylation of JNK and p38 MAPK were elevated in the retinas of 6- and 12-month old Igf1−/− mice compared to those in age-matched Igf1+/+ controls. In 6-month-old Igf1−/− retinas, increased mRNA levels of the autophagy mediators Becn1, Atg9, Atg5 and Atg4, decreased p62 (also known as SQSTM1) protein expression together with an increased LC3-II:LC3-I ratio reflected active autophagic flux. However, in retinas from 12-month-old Igf1−/− mice, Nlrp3 mRNA, processing of the IL1β pro-form and immunostaining of active caspase-1 were elevated compared to those in age-matched Igf1+/+ controls, suggesting activation of the inflammasome. This effect concurred with accumulation of autophagosomes and decreased autophagic flux in the retina. Microglia localization and status of activation in the retinas of 12-month-old Igf1+/+ and Igf1−/− mice, analyzed by immunostaining of Cd11b and Iba-1, showed a specific distribution pattern in the outer plexiform layer (OPL), inner plexiform layer (IPL) and inner nuclear layer (INL), and revealed an increased number of activated microglia cells in the retina of 12-month-old blind Igf1−/− mice. Moreover, reactive gliosis was exclusively detected in the retinas from 12-month-old blind Igf1−/− mice. In conclusion, this study provides new evidence in a mouse model of IGF-1 deficiency that autophagy is an adaptive response that might confer protection against persistent inflammation in the retina during ageing.